2015
DOI: 10.1002/2015ja021685
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of midlatitude E region echoes observed by the Hokkaido SuperDARN HF radar

Abstract: Statistical characteristics of short‐range coherent echoes observed by the Hokkaido Super Dual Auroral Radar Network (SuperDARN) high‐frequency (HF) radar (geographic/geomagnetic latitude = 43.5°N/37.3°N) at midlatitudes are investigated. We show that the echo occurrence is increased during nighttime and, especially strongly, during winter and summer. During summer, the occurrence rates are still large during morning‐prenoon hours; for these periods, strong sporadic E layers are observed by the Wakkanai ionoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…This process is particularly important at mid-latitudes where magnetospheric electric fields are weak. Yakymenko et al (2015) found that the diurnal variation of HOK echo velocity at short ranges cannot be explained by variation in the E × B drift alone. However, by adding a neutral wind contribution to the irregularity velocity and assuming that the irregularities were not strictly magnetic field-aligned, they were able to match the measurements with theoretical expectations.…”
Section: Ion-neutral Coupling and Generation Of Plasma Irregularitiesmentioning
confidence: 90%
See 3 more Smart Citations
“…This process is particularly important at mid-latitudes where magnetospheric electric fields are weak. Yakymenko et al (2015) found that the diurnal variation of HOK echo velocity at short ranges cannot be explained by variation in the E × B drift alone. However, by adding a neutral wind contribution to the irregularity velocity and assuming that the irregularities were not strictly magnetic field-aligned, they were able to match the measurements with theoretical expectations.…”
Section: Ion-neutral Coupling and Generation Of Plasma Irregularitiesmentioning
confidence: 90%
“…Koustov et al (2014) performed a more comprehensive analysis of E region MSTID signatures in HOK echoes and reported preferential occurrence of such echoes in summer with a secondary maximum in winter. This tendency is despite the fact that E region nighttime HOK echoes are more frequent in winter (Yakymenko et al 2015). The authors found the E region MSTIDs propagate toward the southeast or east during pre-midnight hours and toward the southwest or west during post-midnight hours with average speeds of 86 m s −1 and 56 m s −1 , respectively.…”
Section: Nighttime Mstids: E Region Signatures and Vertical Couplingmentioning
confidence: 95%
See 2 more Smart Citations
“…Unfortunately, the amount of high‐quality data for the case of SuperDARN is extremely limited (Davies et al, 1999; Gillies et al, 2018; Koustov et al, 2005). Several studies used the velocity of SuperDARN echoes at far ranges as a proxy for the E × B vector at shorter ranges thus assuming ionospheric flows to be uniform (Gorin et al, 2012; Makarevitch et al, 2004; Milan & Lester, 1998; Yakymenko et al, 2015). These studies did not conclude on the relationship quantitatively.…”
Section: Introductionmentioning
confidence: 99%